2023
DOI: 10.3389/feduc.2023.1141620
|View full text |Cite
|
Sign up to set email alerts
|

Integrating COIL in teacher training: An estimation of learners´ motivational attitudes

Abstract: Collaborative Online International Learning experiences have gained popularity and presence in the last years, but the motivational impact they have on future Primary Education teachers in the field of teacher training education is to be researched. We present a quantitative study that tries to estimate the level of motivation of teacher training students that are in the trilingual degree in the Basque Country. This study examines the level of confidence, attention, satisfaction and relevance of learners in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Research has also shown the potential of COIL in initial teacher training, as it is a powerful tool to bring attractive and globally relevant learning experiences to the classroom (Quintana-Ordorika et al , 2023; Slapac et al , 2023). Be that as it may, it still seems pertinent to explore the perceptions of future teachers regarding the educational benefits of COIL, especially with regard to the development of learners’ intercultural skills.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown the potential of COIL in initial teacher training, as it is a powerful tool to bring attractive and globally relevant learning experiences to the classroom (Quintana-Ordorika et al , 2023; Slapac et al , 2023). Be that as it may, it still seems pertinent to explore the perceptions of future teachers regarding the educational benefits of COIL, especially with regard to the development of learners’ intercultural skills.…”
Section: Introductionmentioning
confidence: 99%